CD30 (Ki-1) molecule expression in human embryonal epithelial cells of the basal layer of the developing epidermis and epidermal buds and its potential significance for embryogenesis - Tamiolakis, Dimitrios (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Objective: CD30 antigen has long been considered to be restricted to tumour cells of Hodgkin's disease, of anaplastic large cell lymphoma and T and B activated lymphocytes. Expression of CD30 antigen has been reported in the decidual stroma, cultivated macrophages, lipoblasts, myoepithelial cells, reactive and neoplastic vascular lesions, mesotheliomas, embryonal carcinoma and seminoma cells. The fact that the CD30 molecule can mediate signals for cell proliferation or apoptosis prompted us to perform a systematic investigation of CD30 antigen expression in embryonal tissues during the proliferation and differentiation stages. We first targeted foetal human intestinal cryptae cells with positive results. The epidermis is a dynamic epithelium that is constantly renewed throughout life. Its turnover is estimated at about 7 days in mice and about 60 days in humans. This rapid replacement demands, as with other epithelial tissues, that an adult has stem cells capable of supplying differentiated cells throughout life. The most basic and widely accepted criteria for these stem cells are that they have a high capacity for self-renewal and the ability to generate daughter cells thatundergo terminal differentiation. Not all of the proliferative cells in the basal layer are stem cells and we were intrigued to find out if stem or other cells in the basal layer can express the CD30 antigen. Materials and methods: We investigated the immunohistochemical expression of CD30 antigen in15 paraffin-embedded tissue samples representing epidermis and epidermal buds from foetuses after spontaneous abortion in 8th, 10th, and 12th week of gestation, respectively, using the monoclonal antibody Ki-1.(Abstract truncated at 2000 characters)
Keywords: Antigeni, CD30; Antigens, Cd30; embriologija; Embryology; Epidermis; epitel; Epitelij; Epithelium; Gestacijska starost; Gestational Age; histologija; Immunohistochemistry; Imunohistokemija; koža